Transposon Mutagenesis Identifies Novel Genes Associated with Staphylococcus aureus Persister Formation - Wang, Wenjie; Chen, Jiazhen; Chen, Gang; Du, Xin; Cui, Peng; Wu, Jing; Zhao, Jing; Wu, Nan; Zhang, Wenhong; Li, Min; Zhang, Ying (Frontiers in Microbiology, 2015)
Pathogenic bacterial persisters are responsible for the recalcitrance of chronic and persistent infections to antimicrobial therapy. Although the mechanisms of persister formation and survival have been widely studied in Escherichia coli, persistence mechanisms in S. aureus remain largely unknown. Here, we screened a transposon mutant library of a clinical methicillin-resistant Staphylococcus aureus（MRSA）strain, USA500 (ST8), under antibiotic pressure and identified 13 genes whose insertion mutations resulted in a defect in persistence. These candidate genes were further confirmed by evaluating the survival of the mutants upon exposure to levofloxacin and several other stress conditions. We found 13 insertion mutants with significantly lower persister numbers under several stress conditions, including sdhA, sdhB, ureG, mnhG1, fbaA, ctaB, clpX, parE, HOU_0223, HOU_0587, HOU_2091, HOU_2315 and HOU_2346, which mapped into pathways of oxidative phosphorylation, TCA cycle, glycolysis, cell cycle and ABC transporters, suggesting that these genes and pathways may play an important role in persister formation and survival. The newly constructed knockout strains of ureG, sdhA and sdhB and their complemented strains were also tested for defect in persisters following exposure to levofloxacin and several other stress conditions. The results from these experiments were consistent with the screening results, which indicated that deletion of these genes in MRSA USA500 leads to persister defect. These findings provide novel insights into the mechanisms of persister formation and survival in S. aureus and offer new targets for the development of persister-directed antibiotics for the improved treatment of chronic and persistent infections.